KOMITMEN PENUH WORLD HEALTH ORGANIZATION (WHO) DALAM PENDISTRIBUSIAN VAKSIN CORONAVIRUS DISEASE (COVID-19) DI INDONESI - Muchammad Farid; Mochammad Alifano (Universitas Pendidikan Muhammadiyah Sorong, 2022)
Coronavirus Disease (COVID-19) began to enter Indonesia from March 2020 until now. The Government of Indonesia through the Ministry of Health of the Republic of Indonesia, the National Disaster Management Agency and related agencies are committed and fully coordinated both at the regional and central levels in dealing with the pandemic by means of the Covid-19 Vaccination program. This Covid-19 vaccine comes from a real commitment from the World Health Organization (WHO) as the World Health Organization for the country of Indonesia in preventing the spread of Covid-19 in Indonesia, to support the strategic policy of comprehensive national Covid-19 vaccination, and to form a Herd. Immunity in the Republic of Indonesia. The research method used is the document study method from the results of pre-existing research by searching online scientific journals. With the results of this academic work (Journal) readers are expected to understand and be able to analyze properly regarding the handling of the Covid-19 pandemic at the local government level, central government level and WHO's full commitment in distributing the Covid-19 vaccine in the Republic of Indonesia Abstrak: Coronavirus Disease (COVID-19) mulai masuk ke negara Indonesia mulai bulan maret 2020 hingga saat ini. Pemerintah Indonesia melalui Kementerian Kesehatan Republik Indonesia, Badan Nasional Penanggulangan Bencana dan Instansi terkait berkomitmen dan berkoordinasi penuh baik tingkat daerah maupun pusat dalam penanggulangan pandemi tersebut dengan cara program Vaksinasi Covid-19. Vaksin Covid-19 ini berasal dari bentuk komitmen nyata dari World Health Organization (WHO) sebagai Organisasi Kesehatan Dunia untuk negara Indonesia dalam mencegah persebaran Covid-19 di Indonesia, untuk mendukung kebijakan strategis yakni Vaksinasi Covid-19 secara nasional menyeluruh, dan untuk membentuk Herd Immunity (Kekebalan Kelompok) di negara Republik Indonesia. Metode penelitian yang digunakan ialah metode studi dokumen dari hasil penelitian yang sudah ada sebelumnya dengan penelusuran jurnal ilmiah online. Dengan adanya hasil karya akademik ini (Jurnal) pembaca diharapkan memahami dan dapat mampu menganalisa dengan baik terkait penanggulangan pandemi Covid-19 dalam skala tingkat pemerintah daerah, tingkat pemerintah pusat dan komitmen penuh WHO dalam pendistribusian Vaksin Covid-19 di Negara Republik Indonesia. Kata Kunci: WHO 1; Koordinasi Penanganan Covid-19 2; Vaksinasi Covid-19 3.